2021
DOI: 10.3389/fonc.2021.591502
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Radiomics Features Extracted From Computed Tomography in Patients With Localized Clear Cell Renal Cell Carcinoma After Nephrectomy

Abstract: Background and purposeRadiomics is an emerging field of quantitative imaging. The prognostic value of radiomics analysis in patients with localized clear cell renal cell carcinoma (ccRCC) after nephrectomy remains unknown.MethodsComputed tomography images of 167 eligible cases were obtained from the Cancer Imaging Archive database. Radiomics features were extracted from the region of interest contoured manually for each patient. Hierarchical clustering was performed to divide patients into distinct groups. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In particular, our radiomic signature can better identify both benign and malignant lesions succeeding in the aim of decreasing the overtreatment and of better delineating a malignancy risk stratification and subsequent approach for malignant SRMs. Moreover, these data can be implemented with clinical, deep learning, radiometabolomics, SPECT and transcriptomics data [ 29 , 30 , 31 , 32 , 33 ] to improve performances. Klontzas et al [ 32 ] showed that the radiomics-only performance for distinguishing benign from malignant renal masses was 70%, while the integration of radiomics and metabolomics increased the performance in differentiating malignant lesions (solid, cystic or mixed) to at least 86%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, our radiomic signature can better identify both benign and malignant lesions succeeding in the aim of decreasing the overtreatment and of better delineating a malignancy risk stratification and subsequent approach for malignant SRMs. Moreover, these data can be implemented with clinical, deep learning, radiometabolomics, SPECT and transcriptomics data [ 29 , 30 , 31 , 32 , 33 ] to improve performances. Klontzas et al [ 32 ] showed that the radiomics-only performance for distinguishing benign from malignant renal masses was 70%, while the integration of radiomics and metabolomics increased the performance in differentiating malignant lesions (solid, cystic or mixed) to at least 86%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Klontzas et al [ 30 ], by combining the 99m Tc Sestamibi uptake with radiomics in distinguishing benign oncocytic neoplasia, increased the diagnostic accuracy and improved positive and negative predictive value. Finally, transcriptomics and radiomics have been combined to assess the prognosis of RCC patients, as mentioned by Tang et al [ 29 ] (C-index: 0.927 and 0.879 for OS- and DFS-predicting, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that radiomics can predict the prognosis of malignant tumors such as gastric cancer, [15] non-small-cell lung cancer, [16,17] and clear cell renal cell carcinoma. [18,19] This study aimed to establish a combined model based on image features extracted from preoperative MR images to predict recurrence-free survival (RFS) in patients with TNBC.…”
Section: The Authors Have No Funding and Conflicts Of Interest To Dis...mentioning
confidence: 99%
“…Many studies have demonstrated that radiomics can predict the prognosis of malignant tumors such as gastric cancer, [ 15 ] non-small-cell lung cancer, [ 16 , 17 ] and clear cell renal cell carcinoma. [ 18 , 19 ]…”
Section: Introductionmentioning
confidence: 99%